TOBACCO INDUSTRY LABOR MANAGEMENT COMMITTEE NATIONAL STRATEGY (Tufts Archival Research Center, 2007)
Confidential; Tobacco Industry Labor Management Committee (TILMC) report on national strategy. Discusses involvement with indoor air quality issues and their allies in this area. Covers activity surrounding cigarette excise tazes and groups from which the LMC can count for support. Notes funding granted to each group. Summarizes LMC state programs and infrastructure. Lsits administrative costs.